Size selection of Greenland halibut (Reinhardtius hippoglossoides) in the Norwegian bottom trawl fishery with a newly developed double grid system - Larsen, Roger B.; Herrmann, Bent; Sistiaga, Manu Berrondo; Grimaldo, Eduardo; Brinkhof, Jesse; Tatone, Ivan (Journal of Northwest Atlantic Fishery Science, 2017)
Source at https://doi.org/10.2960/J.v49.m715 . Greenland halibut ( Reinhardtius hippoglossoides ) is a commercially important species in the northeast Atlantic trawl fishery. However, direct fishing for it is not allowed and it can only be harvested as bycatch. We investigated for the first time the size selection of Greenland halibut in a newly developed double steel grid system designed for the cod and haddock bottom trawl fishery. In this sorting system the first grid (lower grid) replaced the lifting panel present in the traditional Sort-V single grid system often applied in the fishery. Thus, it contributed to the fish sorting process and simultaneously guided fish to the second grid (upper grid). However, the results showed that nearly all Greenland halibut escapees left through the second grid. The release efficiency of the first grid was estimated to be low, and only 11% of the Greenland halibut entering the grid zone made contact with this grid in a way that provided a size-dependent release probability. In contrast, the estimations showed that all Greenland halibut, still in the gear after the first grid, made contact with the second grid. However, this contact was suboptimal for size selection of most individuals, as the estimated 50% retention length (based on the morphology of Greenland halibut) was below the expected value. Comparison of the release efficiency of the new double grid system relative to that of the grid systems used in the fishery today revealed that the new system did not improve the release of undersized Greenland halibut. Moreover, we found that the existing Sort-V single grid system released significantly more Greenland halibut than the new double grid system.